Improvement of Quality of Carica papaya L. with Clove Oil as Preservative in Edible Coating Technology - Kusrini, Eny; Usman, Anwar; Wisakanti, Chrispine Deksita; Arbianti, Rita; Nasution, Dedy Alharis (Makara Journal of Technology, 2015)
We have studied utilization of essential clove oil, extracted from clove buds by hydrodistillation, as preservative in edible packaging technology. Preservative of essential clove oil was applied on chopped papaya fruits by using two methods, namely spray and brush. The effects of concentration of clove oil from 0.05 to 0.20% on the preservation of papaya fruits (Carica papaya L.) at room temperature (25 °C) were also evaluated. Physicochemical and in vitro microbiological activities on the papaya fruits that were stored at 25 oC and 85-90% relative humidity were investigated in details. The results indicate that the clove oil at concentration ≥0.10% suppressed the decay time, 10% weight loss, 0.03 g citric acid/100 g in acidity titration test, and 20% pH value from those of control sample of papaya fruits kept in a storage. The population of fungi and bacteria were efficiently reduced by 90% when the clove oil at concentration ≥0.10% was applied as preservative on papaya fruits. This finding suggested that the extracted essential clove oil acted as effective antifungal and antibacterial agents. Preservative by essential clove oil improved the quality of fruits to extend the product shelf life and to reduce the risk of microbial growth on fruits surface.